Analisis Membangun Budaya Dan Iklim Sekolah Dalam Upaya Membentuk Karakter Siswa SMK Swasta Al-Hikmah Pulau Banyak - Risma Handayani, Rani Febriyanni, Ahmad Mukhlasin (Ability: Journal of Education and Social Analysis, 2023)
The school culture and climate applied at SMK Al Hikmah Pulau Banyak is a climate that fosters a commitment to independence in organizing learning activities. Fostering the participation of school members in creating a safe and orderly environment, establishing clearly and realizing the vision by operationalizing the mission into activity programs; realizing cohesiveness and developing good communication through collaborative activities. The school culture that is implemented at Al Hikmah Vocational School through self-development activities, namely: Routine activities, namely activities carried out by students continuously and consistently such as Monday ceremony activities, major state ceremonies, nail hygiene checks, class pickets, congregational prayers, marching when enter class, pray before class starts and ends, and say hello when meeting teachers, educators and friends. School culture is carried out with spontaneous activities, namely activities carried out by students spontaneously at that time, for example, collecting donations when a friend is affected by a disaster or donating to the community when a disaster occurs. The teacher cultivates exemplary behavior, namely the attitude of teachers, education staff and students in setting an example through good actions that are expected. Discipline values ??(teacher's presence earlier than students), cleanliness, tidiness, affection, politeness, attention, honesty and hard work and confidence. Conditioning, namely Conditioning, namely creating conditions that support the implementation of character education, for example cleanliness of the body and clothes, clean toilets, trash cans, green yards with trees, posters of wise words at school and in the classroom. SMK Al Hikmah Pulau Banyak has developed and implementing character building values ??through the operational program of character value education units instilled in the form of religious values, mutual cooperation, cleanliness, discipline, togetherness, caring for the environment, and hard work. The main emphasis is on instilling Islamic religious values ??in students so that they will become generations of skilled and Muslim characters. SMK Al-Hikmah Pulau Banyak in building a school culture and climate which is applied in an effort to shape the character of students through routine and exemplary activities and apply religious values ??as well as possible. Students are given examples and habits in carrying out activities that reflect skills that are supported by religious values.